Advances in understanding the role of immune checkpoint LAG-3 in tumor immunity: a comprehensive review - Luo, Yingzhe; Cai, Xuebin; Yang, Biao; Lu, Facheng; Yi, Cheng; Wu, Guoyu (Frontiers in Oncology, 2024)
Lymphocyte activation gene 3 (LAG-3), also known as CD223, is an emerging immune checkpoint that follows PD-1 and CTLA-4. Several LAG-3 targeting inhibitors in clinical trials and the combination of relatlimab (anti-LAG-3) and nivolumab (anti-PD-1) have been approved for treating -unresectable or metastatic melanoma. Despite the encouraging clinical potential of LAG-3, the physiological function and mechanism of action in tumors are still not well understood. In this review, we systematically summarized the structure of LAG-3, ligands of LAG-3, cell-specific functions and signaling of LAG-3, and the current status of LAG-3 inhibitors under development.